Biphasic bone graft prepared using a gel-foaming technique. Issue 6 (15th March 2021) - Chang, Hao-Yu; Chen, Ying-Cen; Tuan, Wei-Hsing; Hwang, Sseu-Pei; Chang, Li-Kwan; Wu, Chia-Jung; Chen, Chih-Yi; Lai, Po-Liang
Abstract: Synthetic bone graft has gained considerable attention because of an increase in the aged population. In the present study, a biphasic bone graft composed of hydroxyapatite (HAp) and calcium sulfate (CS) is prepared using a gel-foaming technique. The gel is prepared at a temperature as low as 35 °C; many pores are introduced into the gel through an agitation process. The foamed gel can be cut into any shape and size. After sintering, the porosity of the biphasic bone graft is approximately 70%. Depending on the HAp/CS ratio, the amount of macropores and micropores can be tailored. The macropores of approximately 130 μm diameter are interconnected with each other through openings of 40 μm size. The biphasic bone graft exhibits no cytotoxicity; preosteoblast cells can adhere and proliferate on the surface of the fabricated bone graft. However, migration of these cells into the bone graft is considerably limited in the in vitro study. When the biphasic bone graft is implanted into the distal femur of rats, with the combined effect of osteoblast and osteoclast cells, more than 90% of the bone graft is degraded after 3 months. New trabeculae bone and bone marrow are observed within the bone defect. The HAp/CS composite can thus be used as degradable bone grafts.